Synergy of RHA and silica sand on physico-mechanical and tribological properties of waste plasticâreinforced thermoplastic composites as floor tiles - Soni, A. (Springer Science and Business Media Deutschland GmbH, 2022)
The usage of waste for the development of sustainable building materials has received an increasing attention in socio-eco-environment spheres. The rice husk ash (RHA) produced during burning of rice husk and the ever-increasing plastic wastes are useless causing detrimental effects on the environment. This research supports the idea of sustainability and circular economy via utilization of waste to produce value-added products. This research explores the potential of waste plastics, RHA, and silica sand as thermoplastic composite materials. The different composite samples were prepared through waste plastics which includes low- and high-density polyethylene and polypropylene with incorporation of RHA and silica sand in proportions. The study investigates the effect of filler/polymer in 30/70, 20/80, and 10/90 (wt. ) on the workability of the developed composite materials. The workability of the composites was found to improve with filler reinforcement. The experimental results showed the maximum density of 1.676Â g/cm3 and mechanical strength of 26.39, 4.89, and 3.25Â MPa as compressive, flexural, and tensile strengths, respectively. The minimum percentage of water absorption was 0.052. The wear tests resulted in a minimum abrasive and sliding wear rate of 0.03759 (cm3) and 0.00692 Ã 10â6Â kg/m. The correlations between wear mechanisms and responses were morphologically analyzed. The developed composites verify the feasibility of RHA and plastics waste as a cost effective and environmentally competent product. The results and discussions provided a direction for the future research on sustainable polymeric composite materials. Graphical abstract: Figure not available: see fulltext. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.